POTENSI MINYAK MIKROALGA DAN KHAMIR SEBAGAI SUMBER ASAM LEMAK ESENSIAL - Erika Rozana; Sri Haryani Anwar; Muhammad Ikhsan Sulaiman (Jurnal Teknologi Industri Pertanian, 2022)
Edible oils as essential fatty acids sources, such as linolenic acid, eicosapentaenoic acid, anddocosahexaenoic acid, are commonly extracted from plants and seafoods, particularly fish. The productionof fishoil has several drawbacks, including overfishing issues, mercury contamination, and unpleasant smell of fish. Oilproduction from plants requires extensive land used, long harvest time, and high operational costs. Single-cell oilsfrom microorganisms are the solution to overcome these problems. Therefore, this study aimed to explore thepotential of microorganisms, i.e. microalga and yeast, which had previously been isolated from mangrove forestsin Aceh Province, Indonesia, as sources of essential fatty acids. Two types of microorganisms used wereThraustochytrium multirudimentale and Rhodotorula mucilaginosa. The results showed that the highest amountof oil was extracted from yeast (17.04 ± 0.78 mg/g), while microoalga produced 4.50 ± 0.49 mg/g only. Based oncorrelation analysis, the optical density (OD) and biomass, had good correlation with r = 0.990. The spectra ofFT-IR analysis from microalga and yeast oils proved that both contained C=O groups which identified as estersof fatty acids and C=C groups identified as unsaturated fatty acids. Thraustochytrium multirudimentale andRhodotorula mucilaginosa are potential as single-cell oil sources containing essential fatty acids.Keywords: essential oil, fatty acids, microalgae, omega-3, single-cell oil, yeast